Daily inspiration from the monk who sold his ferrari - "Sharma, Robin" (Mumbai, 2008)
This book is very much inspiring for us. The author has explained us all that how should we frame our life. His book are very impactful on a reader's mind.Covering essential topics such as Real Success, Overcoming Adversity and Disappointment, Building Remarkable Relationships, and Impact and Legacy, this beautiful book is certain to become a lifelong companion on your journey toward becoming an extraordinary human being - and leading a life that you will be proud of at the end.
Keywords: Inspiration